Tecnologia Rádio sobre Fibra Aplicada à Extensão de Cobertura de Redes de Telefonia Móvel: Abordagem Experimental Baseada no Padrão LTE-A - Dalarmelina, Carlos Alberto (2018)
A simple and low cost approach for coverage extension of telecommunication services basedon the enhanced long-term evolution (LTE-A), through radio-over-fiber (RoF) technology,is proposed in this Thesis.Simulation results in a back-to-back configuration and after propagation through 20, 40 and60 km of standard single-mode fibers (SSMF), without chromatic dispersion compensation,validate the developed downlink and uplink RoF numerical models, parametrized accordingto the 3GPP releases.Experimental results, of the OFDMA with carrier aggregation and SC-FDMA transmissionsin downlink and uplink, respectively, show the robustness of the implemented RoF systemsaccording to error vector magnitude (EVM) measurements of 17.5, 12.5 and8%for QPSK,16-QAM and 64-QAM subcarrier mapping, respectively. Three subbands, with subcarriersmapped in 64-QAM, were sucessfuly detected (EVM= 6%) in the OFDMA system afterpropagation through 60 km of SSMF in a RoF link with external modulation provided by anoptimized bias Mach-Zehnder optical modulator. The EVM performance of approximatley8% proved the robustness of the 65 Mb/s (20 MHz) SC-FDMA system in a 60 km opticallink with−2dBm fiber input power.Nevertheless, it should be stressed that, the main scientific contribution of this Thesis isrealted to the fact that, it was possible to recover the user control channel in the downlinkRoF after propagation through 40 km of SSMF. The maximum likelihood based detectiontechnique enables a block error-free reception with fiber input power−24dBm.